Efektivitas Pemberian Terapi Akupuntur dalam Mengatasi Nyeri Haid Primer pada Mahasiswi Keperawatan - Strisanti, Ida Ayu Suptika; Rastiti, Ida Ayu Anom; Dharmapatni, Ni Wayan Kesari (Poltekkes Kemenkes Kupang, 2022)
Background: Menstrual pain or dysmenorrhea is characterized by pain in the uterus or lower abdomen during menstruation. Acupuncture, as a complementary and alternative medicine method, has been widely used to treat various health problems related to gynecological problems. This study aimed to determine the effectiveness of acupuncture therapy in reducing menstrual pain scale. Method: This study used One group pre-post-test research design. The research sample was 20 nursing students at ITEKES Bali level II. The data were collected using an observation sheet with a Comparative Pain Scale containing a pain scale of 0-10. Results: In the pretest, there were two responses (10%) with menstrual pain on a scale of 7, 3 respondents (13%) on a scale of 5, and 1 respondent (5%) on a scale of 6 and 2 respondents (10%) with a pain scale of 2. After the intervention in the form of acupuncture, the results obtained were seven respondents (35%) with a pain scale of 0, 10 respondents (50%) with a pain scale of 1, and 2 respondents (10%) with a pain scale of 3. The results of the Wilcoxon test showed an Md value = 3.50 in the pre-intervention decreased significantly to Md=1.00 at the post-intervention with p value 0.012 with r= 0.60 and Z= 3.975. Conclusion: This study shows that acupuncture effectively reduces the pain scale in female students who experience menstrual pain.